PREPARATION AND SOCIALIZATION OF THE USE OF BRAND GUIDELINESS IN AN EFFORT TO BUILD THE IMAGE OF IAIN METRO - Faizah, Iva; Daniyati, Wiwi Dwi; Sutik, Sarto (Universitas Islam Negeri Raden Intan Lampung, 2024)
Brand Guidelines are guidelines for using an institution's brand or logo which are used as the identity of the institution and play a role in increasing institutional accountability, enhancing the positive image of the institution and supporting promotional activities. Brand guidelines contain a series of regulations regarding the meaning, philosophy, and use of a brand or logo and its application in various media, ranging from print media, electronic media, indoor media, and outdoor media. Service activities by making guidelines for the use of this brand or logo are carried out at IAIN Metro Lampung, which aims to carry out the preparation and socialization of the use of the IAIN Metro logo that is correct in size, color, shape, and precision, as well as uniform and consistent application by all IAIN academics Metro. There were 3 service sessions conducted using the ABCD (Asset Based Community Development) service research method, namely: 1). Preparation (study of case analysis, collection of required information data such as IAIN Metro STATUTE), 2). Implementation (planned regarding content layout and brand guidelines, compiling a draft of the decree as the legality of brand guidelines and dissemination of the use of brand guidelines), 3). Reporting The results of this service activity show that there are still many academics who are wrong in using the IAIN Metro logo, both in terms of terrain, size and position, this service activity received a positive response from all socialization participants and IAIN Metro institutions.